Factores de riesgo asociados a síndrome metabólico en pacientes de 25 a 50 años en la ciudad de Cariamanga en el periodo enero-junio del 2016. - Valle Imaicela, Luis Alberto (2017)
The present study was based on a cross - sectional prospective study carried out in the city of Cariamanga in the office of Dr. Jorge Víctor Imaicela Vicente, whose objective was to determine the risk factors associated with metabolic syndrome in patients aged 25 to 50 years in the city of Cariamanga in private consultation of the medical center Dr. Jorge Imaicela. For that, we analyzed 100 patients who go to outpatient clinic, of which 60% have metabolic syndrome and 40% do not present the metabolic syndrome; who were assessed weight, height, blood pressure, abdominal perimeter, fasting basal glycemia, HDL-C and triglycerides; estimating the metabolic syndrome according to the ATP III criteria. In the results, a prevalence of metabolic syndrome of 60% that presented metabolic syndrome was estimated, whereas 40% did not present this syndrome. The study showed that the researched population presented a 60% metabolic syndrome, constituting a public health problem, so it is pertinent the implementation of intervention strategies aimed at its prevention and early diagnosis. Key words: Metabolic syndrome, prevalence, diagnostic criteria, triglycerides, ATP III.